Associations Between Children's Depressive Symptoms, Life Events, and Family Factors Among School‐Aged Children. (21st November 2022) - Talja, Tiina; Rantanen, Anja; Koivisto, Anna‐Maija; Helenius, Jenni; Joronen, Katja
ABSTRACT: BACKGROUND: About 20‐30% of children worldwide report depressive symptoms. This study examined associations between children's depressive symptoms, life events, and family factors. METHODS: Nationally representative data (n = 95, 725) were drawn from the 2017 School Health Promotion Study in Finland. The respondents were 4th and 5th grade pupils (aged 10‐12) in primary schools and their parents/guardians (n = 33, 726). Data were analyzed for child‐parent dyads (n = 32, 181). Associations were studied using cross tabulation and logistic regression models. RESULTS: Children's reports of poor self‐rated health, problems with family interactions, and the accumulation of life events were statistically significantly associated with depressive symptoms, also when controlling for sociodemographic factors. Financial situation and parent's depressed mood, both reported by parents, were associated with children's depressive symptoms when both were included in the regression model. However, this association disappeared when other predictors were added to the model. CONCLUSION: The results make apparent the complex associations between children's depressive symptoms and family factors. Further research is needed on the discrepancies between parent and child experiences.